Store profitability and public policies to improve food access in non-metro U.S. counties. (February 2018) - Cleary, Rebecca; Bonanno, Alessandro; Chenarides, Lauren; Goetz, Stephan J.
Highlights: Compares the cost-effectiveness of demand-side and supply-side policies to mitigate food access issues. Uses an economic model of large food-store entry to compare policies in non-metro U.S. counties. Relative effectiveness of each policy type cannot be determined a priori and depends upon metro-adjacency,  store size, and number of stores. Improving SNAP coverage is more cost-effective in metro-adjacent counties and counties with at least one large food store. Abstract: Access to affordable and nutritious food is a widely-debated public policy issue in the U.S. In non-metro (including semi-urban and rural) U.S. areas, poor food access is mostly the result of lack of food stores, and in particular the absence of large ones ( e.g., full-line groceries or superstores). Any policy designed to improve food access in non-metro U.S. areas should recognize that improving stores' profitability is crucial to policy success in the long-run. We adapt an empirical entry model to assess the effectiveness of two types of policies to improve food access – demand-stimulating policies (DSP), such as increases in Supplemental Nutrition Assistance Program dollars, and supply-side policies (SSP), such as subsidies to reduce establishment costs – by estimating the minimum market size needed for one or more large food stores in non-metro U.S. counties to be profitable. We find that neither type of intervention is preferred a priori and that the cost-effectiveness of each policy type depends upon the presence of an adjacent metropolitan county, the number of pre-existing stores, and the duration of the demand-side stimuli. Additionally, our results suggest that the cost-effectiveness of broad-based policy solutions to improve physical access to large food stores or to stimulate demand may be limited when it comes to easing entry in areas with multiple stores.